Platelet Aggregation, Fibrinogen And Lipid Profile In Cerebrovascular Accidents - M. BALACHANDIRAN,; DR .C.SELVAKUMAR.,; DR. M.G. SRIDHAR, (International Journal of Pharma and Bio Sciences, 2012)
Platelet aggregation is the one of the initial haemostatic events that stops bleeding resulting from a vascular injury. It has been observed that increased collagen induced platelet aggregation in acute ischemic stroke patients. In view of the above, the present study was planned to determine the above said parameter in acute ischemic stroke patients. A total number of 60 subjects participated in the present study which included 30 acute ischemic stroke cases and 30 controls. Fasting plasma glucose, lipid profile, Plasma fibrinogen, Platelet aggregation were estimated. Platelet aggregation was significantly lower in cases (acute ischemic stroke) as compared to controls; whereas collagen induced platelet aggregation and plasma fibrinogen were significantly higher in cases. No significant differences were found in triglycerides, HDL – cholesterol, VLDL, TG/HDL and Atherogenic Index. In present study we found an increased collagen induced platelet aggregation which is induced by plasma fibrinogen and positive correlation between atherogenic index and fibrinogen.